IMPLEMENTATION OF DIFFERENTIATED LEARNING ON CULTURAL ARTS SUBJECTS IN SENIOR HIGH SCHOOL: IMPLEMENTASI PEMBELAJARAN BERDEFERENSIASI PADA MATA PELAJARAN SENI BUDAYA DI SEKOLAH MENENGAH ATAS - Daryanti, Fitri; Wendhaningsih, Susi; Gustia ningsih, Lora (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
The purpose of this research is to identify the implementation of differentiated learning in cultural arts subjects at SMAN 2 Kalianda. This research is a qualitative research, data collection was conducted through observation, interview, and documentation. Data analysis was conducted using Miles and Huberman interactive data analysis, starting from the reduction, display, and conclusion stages. Based on data analysis, the results show that differentiated learning is carried out by teachers using several steps, the first step is the teacher mapping the learning needs of students by analyzing three aspects of students' learning readiness, learning styles, and digging up information about students' interests. The second step is to design a learning strategy using the peer tutor method. Step three teachers carry out learning in accordance with the differentiated learning implementation plan that has been made, using the content differentiation approach, process differentiation and product differentiation. Step four teachers evaluate and reflect on learning to determine the achievement of learning objectives. The implementation of differentiated learning is very important and appropriate to be applied in SMAN 2 Kalianda which is located in the coastal area with different economic backgrounds, characteristics, socio-cultural conditions. The impact of the implementation of differentiated learning in this school shows that, students who have indigenous cultural background become motivated to learn the material, this can be seen from the implementation of content, process, and product differentiation. The results vary according to the learners' characters, learners are happy to get attention from the teacher, and learners' learning needs are well facilitated.